See Answer

### Answer with Explanation

Answer is 108.

**How?**

2 + 3 = 2 *(2+3) = 10

8 + 4 = 8*(8+4) = 96

7 + 2 = 7*(7+2) = 63

6 + 5 = 6*(6+5) = 66

9 + 3 = 9*(9+3) = 108

See AnswerHide Answer

Answer is 108.

**How?**

2 + 3 = 2 *(2+3) = 10

8 + 4 = 8*(8+4) = 96

7 + 2 = 7*(7+2) = 63

6 + 5 = 6*(6+5) = 66

9 + 3 = 9*(9+3) = 108

See AnswerHide Answer

Answer is 3.

**How?**

It simple, but you have to think more then the math ðŸ™‚

1 = one = 3 letters

2 = two = 3 letters

3 = three = 5 letters

4 = four = 4 letters

5 = five = 4 letters

6 = six = 3 letters

See AnswerHide Answer

Answer is 16.

**How?**

Its a little trickier one then others.

sqr root(64) * 5 = 40

sqr root(81) * 7 = 63

sqr root(16) * 4 = ? = 16.

See AnswerHide Answer

Answer is 6.

**How?**

It is the simple subtraction as we used to do in our early maths classes in our childhood, so just reminds us of those days of taking carry and subtracting.

See AnswerHide Answer

Answer is 9.

**How?**

Here, every element in second row = corresponding column element in first row * 2.

Similarly every element in third row = corresponding column element in first row * 3.

See AnswerHide Answer

Answer is 30.

**How?**

Sum of the numbers on vertices of a triangle should be 90, i.e. 20 + 40 + ? = 90 => ? = 30.

See AnswerHide Answer

Answer is 6.

**How?**

Here, Number in a block is sum of the number on the top and right block so 7 = 1 + ?, hence ? should be 6.

Answer is 0 OR 16.

**How?**

Here, there is no special pattern except that they are continuous numbers which are jumbled up, so the missing number can either be 0 or 16.

See AnswerHide Answer

Answer is 9.

**How?**

Here, every middle element is the sum of the other two so answer should be 6+3 = 9.

by Ankur 4 Comments

See AnswerHide Answer

Answer is 54325

How?

Just keep appending the new number to the previous answer ðŸ™‚